PENDAMPINGAN PASTORAL BAGI NARAPIDANA YANG AKAN BERAKHIR MASA TAHANAN (TINJAUAN ASPEK SOSIAL) - Alvin Koswanto (Vox Dei: Jurnal Teologi dan Pastoral, 2020)
The existence of a community stigma against ex-convicts is a phenomenon that still often occurs when prisoners leave the correctional institution. Denial of their presence makes ex-inmates reluctant to socialize normally. This study intends to determine how the role of the Salemba Penitentiary in preparing prisoners to face the end of their detention in terms of social aspects. The method used in this research is qualitative. In conducting this research, researchers came to the Salemba Penitentiary to obtain the required data. Researchers conducted interviews with three sources, namely Christian Spiritual Guidance, several Christian prisoners who have participated in the assistance process at the Correctional Institution, and the YASINDO foundation, where the foundation accepts ex-convicts before being exploited in society. The results of this study, it was found that the aspect of social development has not been able to help inmates to return to life in the wider community. Prisoners who are about to finish their detention still have worry or fear. This is due to the lack of time facilities to participate in the coaching.